Enriched rhizospheric functional microbiome may enhance adaptability of Artemisia lavandulaefolia and Betula luminifera in antimony mining areas - Xing, Wenli; Gai, Xu; Xue, Liang; Li, Shaocui; Zhang, Xiaoping; Ju, Feng; Chen, Guangcai (Frontiers in Microbiology, 2024)
Dominant native plants are crucial for vegetation reconstruction and ecological restoration of mining areas, though their adaptation mechanisms in stressful environments are unclear. This study focuses on the interactions between dominant indigenous species in antimony (Sb) mining area, Artemisia lavandulaefolia and Betula luminifera, and the microbes in their rhizosphere. The results revealed that soil environmental factors, rather than plant species, had a more significant impact on the composition of the rhizosphere microbial community. Soil pH and moisture significantly affected microbial biomarkers and keystone species. Actinobacteria, Proteobacteria and Acidobacteriota, exhibited high resistance to Sb and As, and played a crucial role in the cycling of carbon, nitrogen (N), phosphorus (P), and sulfur (S). The genes participating in N, P, and S cycling exhibited metabolic coupling with those genes associated with Sb and As resistance, which might have enhanced the rhizosphere microbes' capacity to endure environmental stressors. The enrichment of these rhizosphere functional microbes is the combined result of dispersal limitations and deterministic assembly processes. Notably, the genes related to quorum sensing, the type III secretion system, and chemotaxis systems were significantly enriched in the rhizosphere of plants, especially in B. luminifera, in the mining area. The phylogenetic tree derived from the evolutionary relationships among rhizosphere microbial and chloroplast whole-genome resequencing results, infers both species especially B. luminifera, may have undergone co-evolution with rhizosphere microorganisms in mining areas. These findings offer valuable insights into the dominant native rhizosphere microorganisms that facilitate plant adaptation to environmental stress in mining areas, thereby shedding light on potential strategies for ecological restoration in such environments.